"Ocorrência de Ehrlichia spp., Anaplasma spp., Babesia spp., Hepatozoon spp. e Rickettsia spp. em cães domiciliados em seis municípios do Estado do Espírito Santo, Brasil" - Vieira, Fernanda de Toledo (2017)
Tick-borne diseases are an important cause of morbidity and mortality in dogs (Canis lupus familiaris) worldwide, with the tick Rhipicephalus sanguineus sensu lato (s.l.) as a vector of various agents. It is very important to know the prevalence of these diseases, their vectors and hosts in order to control and prevent them in the given region. Tick-borne diseases have importance for both veterinary medicine and for public health. This work aims to identify and quantify the percentage of infection by Rickettsia spp., Ehrlichia spp., Babesia spp. and Hepatozoon spp. in pet dogs and identify ticks collected on these animals in the municipalities of Santa Teresa, Colatina, Alegre, Vila Velha, Vitória and Serra. The study included 378 dogs, 226 females and 152 males, of various breeds and ages (mean 4.1 years) with ectoparasites (ticks) or parasitism recent history (30 days). Of the 378 dogs examined, 157 (41.53%) had ticks at the time of consultation, which were identified as R. sanguineus s.l. in 154 animals (98.1%), Amblyomma ovale in one animal (0.63%) and Amblyomma sculptum in 2 animals (1.27%). All animals were examined and whole blood were collected and processed by molecular tests: Real Time PCR for Ehrlichia canis, and conventional PCR protocols for Babesia spp., Hepatozoon spp., and for Anaplasmataceae. In the Real Time PCR specific for E. canis, 28 animals (7.4%) were positive. For Anaplasmataceae, 34 animals (9%) were positive, of which 10 generate DNA sequences with 100% similarity with Ehrlichia canis and the other 24 samples generated fragments 100% identical to Anaplasma platys. In the PCR for Babesia spp., 5 animals (1.3%) were positive, producing DNA sequences 100% identical to Babesia vogeli. Finally, 39 animals (10.31%) were positive by PCR for Hepatozoon spp., producing sequences 100% identical to Hepatozoon canis. It was observed coinfection with 2 or 3 agents in 22 animals (5.8%). Of the 378 dogs in the study, 312 had serum samples collected for serological tests: indirect immunofluorescence assay (IFA) for E. canis, with positive reaction in 71 animals (22,75%) and five species of Rickettsia (R. rickettsii, R. parkeri, R. amblyommatis, R. rhipicephali and R. bellii). Among the sera analyzed by IFA, 16 animals (5.13%) had titers ≥ 64 for at least one species of Rickettsia of the five tested, and 5 (1.6%) of those had titers ≥ 64 for R. rickettsii. These results indicate that some of the studied municipalities have agents transmitted by ticks circulating in the canine population, such as E. canis, A. platys, B. vogeli, H. canis, and possibly spotted fever group rickettsiae.